2009
DOI: 10.2147/cia.s3787
|View full text |Cite
|
Sign up to set email alerts
|

Tolcapone: review of its pharmacology and use as adjunctive therapy in patients with Parkinson's disease

Abstract: Levodopa has been the gold standard therapy for the motor symptoms of Parkinson's disease for more than three decades. Although it remains the most effective treatment, its long-term use is associated with motor fl uctuations and dyskinesias that can be disabling for patients and diffi cult for physicians to manage medically. In the last 10 years, the catechol-O-methyltransferase (COMT) inhibitor tolcapone has been studied for its effi cacy as an adjunctive treatment to levodopa plus a dopa decarboxylase inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 45 publications
0
29
0
1
Order By: Relevance
“…A follow-up of 30 patients showed that bilateral high frequency subthalamic stimulation improved insomnia symptoms [61]. Insomnia has been reported as a side effect of rotigotine [62], selegiline [63], tolcapone [64] and reboxetine [65]. In summary, controlled trials involving a large number of patients that evaluate nocturnal performance and daytime consequences are required to reach any conclusions.…”
Section: Sleep Disordersmentioning
confidence: 99%
“…A follow-up of 30 patients showed that bilateral high frequency subthalamic stimulation improved insomnia symptoms [61]. Insomnia has been reported as a side effect of rotigotine [62], selegiline [63], tolcapone [64] and reboxetine [65]. In summary, controlled trials involving a large number of patients that evaluate nocturnal performance and daytime consequences are required to reach any conclusions.…”
Section: Sleep Disordersmentioning
confidence: 99%
“…These findings furthermore provide the bases for considering therapeutic interventions of COMT including tolcapone, an inhibitor of COMT [62] .…”
Section: The Glutamate Hypothesis Of Schizophreniamentioning
confidence: 82%
“…11 Tolcapone arrived on the market in 1997/1998 and its side effects include elevated liver transaminases and hepatotoxicity. 21 …”
Section: Tolcaponementioning
confidence: 99%